Measuring GHG Mitigation in Agricultural Value Chains - Richards, Meryl B. (2018)
The presentation Measuring GHG Mitigation in Agricultural Value Chains is by Meryl Richards, science officer at CCAFS Low Emissions Development. Presented at the WBCSD Climate Smart Agriculture workshop at the University of Vermont, Burlington, VT on 27 March 2018.